PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL - Daniel Bouman Hasurungan Sinaga; Dul Mu’id (Diponegoro Journal of Accounting, 2015)
This   study aims   to   obtain empirical evidence about the influence of     the   audit committee  characteristics  which consist of proportion of the audit committee size, audit committee meetings   and   audit committee expertise that influencing   the intellectual capital disclosure. This research is replication with modification of the research Ningsih (2014).The population used in this study is all publicly traded companies listed on the Indonesia  Stock  Exchange  in  2013  with  sample  were  181  companies.  The  sampling method used in this study is random sampling. The data used is secondary data that are audited annual report in 2013 which has been published and the data on the date of publication of   financial statements. This study uses the technique of multyple linear regression analysis.The results of this research showed that proportion of audit committee size and audit committee expertise not significantly effect intellectual capital disclosure. While the frequency of audit committee meetings significantly intellectual capital disclosure and also one variables control which used in this research, ROA have significantly effect to intellectual capital disclosure but board independence, listing age, and sales do not have significant effect intellectual capital disclosure.